Asymmetric Price Transmission with Threshold Behavior of Potatoes Market in Bandung Regency West Java - Fitria, Dina Nurul; Harianto, Harianto; Priyarsono, Dominicus Savio; Achsani, Noer Azam (Universitas Muhammadiyah Yogyakarta, 2020)
Horticulture products price in Indonesia (for certain commodities) has experienced the issue of volatility, price decline at farm gate stage, due to an increase in supply is not equal to or comparable with price increase at the other stage. This paper endeavors to investigate threshold behavior in asymmetry test by taking the case of potatoes prices in two important state levels of price, i.e. farm gate prices, and retail prices. The observation used monthly price data from January 2009-December 2013. Threshold behavior detected by TAR model that fits in asymmetry testing with two regime. Threshold value is interpreted as a measure of transaction cost between retail to farm gate and increase the quantity supplied, that would create incentive for trade. Research results reveals as per monthly data price adjustment between farm gate to retail not presence of asymmetry price transmission. Asymmetry only reveals within seasonal data, threshold behavior forms margins overshoot of potatoes equilibrium trader’s levels, thus leading to farmer’s decision in profit maximization. Keywords: threshold behavior, asymmetry testing, potatoes, TAR Model, seasonal